The p56lck SH2 domain mediates recruitment of CD8/p56lck to the activated T cell receptor/CD3/zeta complex. - Thome, M; Germain, V; DiSanto, J; Acuto, O (1996)
The CD4 or CD8 co-receptors and the T cell receptor (TCR) are though to interact with the same antigen-presenting major histocompatibility complex molecule in a stable ternary complex. Therefore, the TCR and its co-receptor need to come into close proximity on the surface of the T cell. We have previously shown that the interaction of the p56lck SH2 domain with zeta-associated, tyrosine phosphorylated ZAP-70 and Syk kinases leads to an enhanced association of CD4 with TCR/CD3/zeta complex after CD3 stimulation of Jurkat cells. In this report, we analyzed whether a similar mechanism can mediate recruitment of the CD8 alpha alpha and CD8 alpha beta isoforms to the TCR. We demonstrate in vivo in association of CD8 alpha alpha/p56lck with the tyrosine kinase ZAP-70 after CD3 stimulation of Jurkat cells. A phosphopeptide competing in vitro for the binding of tyrosine phosphorylated proteins to the SH2 domain of p56lck specifically impedes the association of ZAP-70 with CD8 alpha alpha/p56lck without affecting the zeta/ZAP-70 interaction. The same peptide is able to compete for the activation-dependent association of the CD8 alpha alpha or CD8 alpha beta isoform with the TCR/CD3/zeta complex. Moreover, co-precipitation of the TCR with both CD8 isoforms was observed after CD3 stimulation. These findings strongly suggest that the p56lck SH2 domain mediates recruitment of CD8/p56lck to the activated TCR/CD3/zeta complex.